2022
DOI: 10.1177/10567895221095609
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive modelling of a self-healing composite matrix polymer material

Abstract: In this work, a constitutive model of an intrinsically self-healing composite matrix material is presented. The developed model comprises a micro-damage initiation and evolution model, and a healing evolution model, which are combined with the von Mises linear isotropic hardening plasticity. It is implemented into the Abaqus/Standard user material subroutine UMAT and validated using experimental results of static tensile and two-cycle tensile tests performed on partially neutralised poly(ethylene-co-methacryli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The application of microcapsule-based self-healing agent to produce a wind turbine blade was reported to also have a lower degradation rate. [112] According to Ivika et al, [113] autonomous materials that heals damages are considered detrimental to the component and are usually used in structural fibers reinforced polymeric composites, mainly to recover the stiffness. Huang et al [114] designated a self-healing agent for a low technology readiness level (TRL) experiment in which they loaded a 1D vascular-based selfhealing material and a microcapsule-based self-healing material in an carbon fiber polymer composite aircraft component.…”
Section: Self-healing Applicationsmentioning
confidence: 99%
“…The application of microcapsule-based self-healing agent to produce a wind turbine blade was reported to also have a lower degradation rate. [112] According to Ivika et al, [113] autonomous materials that heals damages are considered detrimental to the component and are usually used in structural fibers reinforced polymeric composites, mainly to recover the stiffness. Huang et al [114] designated a self-healing agent for a low technology readiness level (TRL) experiment in which they loaded a 1D vascular-based selfhealing material and a microcapsule-based self-healing material in an carbon fiber polymer composite aircraft component.…”
Section: Self-healing Applicationsmentioning
confidence: 99%
“…In general, foreign-aided self-healing composites include microcapsules, capillaries, and hollow fibers. [22][23][24][25][26][27] Coope et al 28 investigated the self-healing function of composites by embedding a microvascular network design containing a healing agent. They found that the injected healing agent possessed a high healing efficiency and was able to stop the crack extension within the composite when damage occurred.…”
Section: Introductionmentioning
confidence: 99%
“…The damage evolution for the liquid-assisted healing material systems were proposed by (Siroky et al, 2021). A micro-damage initiation and evolution constitutive law has been developed and implemented in FEA by Ivica et al (2022). Han et al (2021) developed a threedimensional micromechanical model to quantitatively explain the self-healing effects of microencapsulated healing agents on the damage induced by microcracks.…”
Section: Introductionmentioning
confidence: 99%
“…The damage evolution for the liquid-assisted healing material systems were proposed by (Siroky et al., 2021). A micro-damage initiation and evolution constitutive law has been developed and implemented in FEA by Ivica et al. (2022).…”
Section: Introductionmentioning
confidence: 99%